Fiscal Multipliers in Ukraine - Mitra, Pritha (IMF Working Papers; Working Paper ;, 2015)
Amid renewed crisis, falling tax revenues, and rising debt, Ukraine faces serious fiscal consolidation needs. Durable fiscal adjustment can support economic confidence and rebuild buffers but what is its overall impact on growth? How effective are revenue versus spending instruments? Does current or capital spending have a larger impact? Applying a structural vector autoregressive model, this paper finds that Ukraine's near-term revenue and spending multipliers are well below one. In the medium-term, the revenue multiplier becomes insignificant (with a wide confidence interval) and the spending multiplier strengthens. Capital and current spending have a similar effect on growth but the capital multiplier remains significant for longer. These results suggest near-term consolidation based on a combination of revenue and spending measures would have a modest impact on growth. At the same time, medium-term policies could minimize the adverse consequences of consolidation on growth by offsetting some current spending cuts with increased capital spending. Given the severe challenges facing the Ukrainian economy, it is important that policymakers apply these results in conjunction with broader considerations such as public debt sustainability, investor confidence, credibility of government policies, and public spending efficiency. Consequently, it may be necessary to rely more on current spending cuts over other types of consolidation measures even though multiplier estimates suggest a more diverse combination of measures.